Exploring Workplace Happiness: Islamic Leadership and Work Ethics Driving Engagement and Helping Behaviour - Rokhman, Wahibur; Atieq, Muhammad Qoes; Ahamed, Forbis; Nasir, Shuana Zafar; Shahid, Sehrish (Islamic Guidance and Counseling Journal, 2025)
Leadership and work ethics, particularly Islamic or faith-based, are crucial indicators of employees’ well-being and work engagement. It increases helping behaviour through motivation and satisfaction levels achieved from a supportive work environment. The research aim is to examine the influence of Islamic leadership and Islamic work ethics on helping behaviour and work engagement through happiness at work to verify this phenomenon, data has been collected from 320 employees working with Small Medium Enterprises (SMEs) across central Java, Indonesia. All question items from all variables are said to be valid with a value of more than 0.7 and reliable with a value of more than 0.5. This is quantitative design research where a convenience sampling technique was employed. Statistical analysis was done through SmartPLS, revealing a direct relationship among all study variables, such as Islamic leadership, to helping behaviours and work engagement. Additionally, the study identified a direct relationship between Islamic work ethics and helping behaviours, except for a link with work engagement; similarly, employees’ happiness at the workplace acts as a mediator in this study. The hypothesis is accepted because the significance value is more than 1.97. While previous studies have examined workplace happiness and engagement broadly, limited attention has been paid to the role of faith-based leadership and ethics within SMEs in culturally diverse settings like Central Java, Indonesia. This study offers a novel perspective by discussing the pivotal role of Islamic leadership and Islamic work ethics in shaping workplace dynamics, particularly helping behaviour and engagement through happiness.